Associations between accumulating job stressors, workplace social capital, and psychological distress on work-unit level: a cross-sectional study - Risto Nikunlaakso; Kaisa Reuna; Tuula Oksanen; Jaana Laitinen (BMC, 2023)
Abstract Background Psychosocial job stressor studies usually examine one exposure at a time and focus on individual workers. In this study we examined the accumulation of work stressors in work units and its association with psychological distress (PD) on work-unit level. We also investigated whether high workplace social capital modifies the effect. Methods We examined survey responses from 813 Finnish health and social services (HSS) work units, comprising 9 502 employees, in a cross-sectional study design. The survey was conducted in 2021. We calculated odds ratios for the association between accumulating job stressors and PD. We also analyzed the interaction between work stressors and the effect modification of high workplace social capital. Results We found that HSS work units with high percentage of employees having high job demands and low rewards (OR 7.2, 95% CI 3.7, 13.8) have an increased risk of higher PD in the work unit. We also found indication of high social capital possibly modifying the effect of job stressors on PD. The results suggest that accumulated job stressors are associated with PD on work unit level, with excess risk for PD compared to the stressors acting separately. Conclusions The results indicate that the effect of accumulating job stressors should be further studied on work-unit level. Participatory organizational-level and work-unit level interventions to tackle job stressors and to improve workplace social capital are warranted.